Employee Engagement and Financial Performance among SMEs in Lagos State, Nigeria - Akinwale, Akeem A.; Ogunyomi, Paul O. (Àgídìgbo: ABUAD Journal of the Humanities, 2018)
This article examines the influence of employee engagement on financial performance of SMEs in Lagos State, Nigeria, using a survey research design with a random selection of 450 respondents from a population of 4,535 small and medium enterprises in Lagos State, Nigeria. Data were collected through a systematic review of the literature and a structured questionnaire. The data obtained from the questionnaire was subjected to descriptive and inferential statistics. The result showed a significant positive relationship between employee engagement and financial performance of SMEs (r = 0.35; p e” 0.01). Employee engagement positively correlated with the financial performance criteria such as profitability, financial strength, operating efficiency, performance stability, level of indebtedness, and ability of the enterprises to raise capital. The findings suggest that employee engagement should be strengthened to enhance the financial performance of SMEs. SMEs can enhance employee engagement through the use of improved employee- management relations, regular training, teamwork, and increase in capacity utilisation rates.